WIRELESS SMART SENSOR BASED DEVICE WITH IOT - K, Krishnaveni; R, Ida Malarselvi; Raja C, R amachandra; R, Priscilla; S, Joseph Vedhagiri; B S, Sathis Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, human’s efforts are reduced due to the technological developments. Similarly, the physically disabled persons are suffering for their basic needs. For such reasons, Smart home system is developed which is more emerging technology which increases the security, comfort and also improves the quality of human’s life. This article focuses a Multi sensor based wheelchair in a smart home monitoring and alerting system for physically disabled person is being proposed. This system provided a security and comfort for the elderly people and also persons with disability. This system consists of a microcontroller board with a several sensors to achieve monitoring motion and authorization etc. This system also has alerting system when these sensor values are exceeded the fixed threshold value, and the system should alert the user and should motivate required safety procedure. To improve a high Alerting capacity, the vibration sensor is placed on the door to detect if the vibration caused by theft. A security alarm system using low processing power chips using Internet of things (IoT) which helps to monitor and get alarms when motion is detected and sends image of the victim to a cloud server. Moreover, when motion is detected, an IoT based application can be used remotely to view the activity and get notifications. The picture of victim is sent directly to a cloud server when the cloud is not available then the data is stored locally on the Raspberry Pi. On Comparing with all other previous works, this system has a high security and takes immediate response for an every task of happenings. Ultrasonic sensors sense the movement of traveller on road if there may be a object or traveller crossing on road these sensors intimated the same and vibration sensor check the traveller proper position if the person met accident it send SMS alert to the caretaker and an GPS tracker linked through IoT monitoring the persons limited location of home place if the person moved beyond the message alert the family their ward crossing beyond their location and may be missed.